Pythagorean fuzzy AHP based risk assessment methodology for hazardous material transportation: an application in Istanbul - Ayyildiz, Ertugrul; Taskin Gumus, Alev (SPRINGER HEIDELBERG, 2021)
Environment and social life are open to hazards, because of the distribution, diffusion, and conversion processes of chemicals contained in hazardous materials. These chemicals are very dangerous. Various precautions should be taken into consideration during the displacement of hazardous materials. Therefore, it is important to identify and minimize the risks in the transportation of hazardous material. This work investigates to identify the critical risk factors and their weights for hazardous material transportation operations. The literature is reviewed, critical risk factors for hazardous material transportation are defined, and data from different experts is collected. A two-level hierarchical structure is established to evaluate risk factors. Then, the experts' evaluations of main and sub-risk factors are consolidated using the modified Delphi method. Weights of main and sub-risk factors are obtained using the Pythagorean fuzzy analytic hierarchy process method. To show the robustness of the proposed decision-making methodology, a sensitivity analysis is conducted.
Keywords: Risk assessment; Petroleum transportation; Hazardous material; Pythagorean fuzzy AHP; ANALYTIC HIERARCHY PROCESS; ENVIRONMENTAL DECISION-MAKING; OCCUPATIONAL-HEALTH; SAFETY; MODEL; QUALITY; LOCATION; NETWORK; DELPHI; MANAGEMENT; Environmental Sciences & Ecology